2012
DOI: 10.1074/jbc.m112.343830
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Dynamics of Gp59-Gp32-Single-stranded DNA (ssDNA), a DNA Helicase Loading Complex Required for Recombination-dependent Replication in Bacteriophage T4

Abstract: Background: Gp59 is required to correctly load DNA helicase during T4 recombination-dependent DNA replication and repair transactions. Results: Gp59 forms helicase loading complexes with clusters of Gp32 (SSB) bound to ssDNA. Conclusion: Gp59 follows Gp32 to single-stranded regions of recombination intermediates to promote strand-specific helicase loading. Significance: Mediator proteins such as Gp59 play critical roles in the regulation of DNA recombination, repair, and replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 44 publications
5
17
1
Order By: Relevance
“…3A and 3B. Effect of I87A Mutation on HLC Remodeling during Helicase Loading on ssDNA-It was previously shown through Gp32F fluorescence assays that the loading of Gp41 helicase remodels the HLC and that this remodeling is dependent on ATP binding (but not hydrolysis) by Gp41 (20) (Fig. 4A).…”
Section: Comparison Of Dna Binding Activities Of Gp59 Wt and I87a-mentioning
confidence: 85%
See 4 more Smart Citations
“…3A and 3B. Effect of I87A Mutation on HLC Remodeling during Helicase Loading on ssDNA-It was previously shown through Gp32F fluorescence assays that the loading of Gp41 helicase remodels the HLC and that this remodeling is dependent on ATP binding (but not hydrolysis) by Gp41 (20) (Fig. 4A).…”
Section: Comparison Of Dna Binding Activities Of Gp59 Wt and I87a-mentioning
confidence: 85%
“…We have also shown that the fluorescence intensity of Gp32F is increased when it is ssDNA-bound and further increased when it is in a helicase loading complex with ssDNA and Gp59 (20,23). This Gp32F fluorescence assay was used to determine the effects of the Gp59-I87A mutation on HLC formation (Fig.…”
Section: Comparison Of Dna Binding Activities Of Gp59 Wt and I87a-mentioning
confidence: 93%
See 3 more Smart Citations